SOCIAL MEDIA ANALYSIS OF CONTRACEPTIVE (CONDOM) USE POLICY FOR STUDENTS AND TEENAGERS IN INDONESIA - Bayu Aulia Priyantomo (PT. Jurnal Center Indonesia Publisher, 2025)
The development of technology, especially in social media, is increasingly developing every year, which is commonly used daily by the public with the aim of obtaining information. The approach used in this study is the Social Media Analytics (SMA) framework to analyze sentiment using NoLimit Indonesia software. Sentiment Analysis is a measurement of sentiment or emotion of social media users based on content analysis (positive/negative/neutral). This study aims to determine the sentiment analysis using the keywords